2012
DOI: 10.1128/jvi.05862-11
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Class of Internal Ribosomal Entry Site in Members of the Kobuvirus and Proposed Salivirus and Paraturdivirus Genera of the Picornaviridae

Abstract: The 5=-untranslated regions (5= UTRs) of picornavirus genomes contain an internal ribosomal entry site (IRES) that promotes the end-independent initiation of translation. Picornavirus IRESs are classified into four structurally distinct groups, each with different initiation factor requirements. Here, we identify a fifth IRES class in members of Kobuvirus, Salivirus, and Paraturdivirus genera of Picornaviridae: Aichi virus (AV), bovine kobuvirus (BKV), canine kobuvirus (CKoV), mouse kobuvirus (MKoV), sheep kob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 94 publications
(157 reference statements)
3
99
0
Order By: Relevance
“…These IRES elements are classified into five types based on sequence and structural homology: type I IRES of the enterovirus group with poliovirus as prototype, type II IRES of the cardiovirus/aphthovirus group with encephalomyocarditis virus (EMCV) and FMDV as prototypes type III IRES of hepatitis A virus (HAV), and type IV IRES of porcine teschovirus (PTV) (Borman et al, 1997;Brown et al, 1991;Jackson et al, 1994;Pisarev et al, 2004). Sweeney et al (2012) and colleagues recently identified a fifth IRES class among members of the Kobuvirus, Salivirus and Oscivirus genera. The nucleotide sequence identity among IRES elements of the same type is only moderate, but their predicted secondary structure is highly conserved.…”
Section: Introductionmentioning
confidence: 99%
“…These IRES elements are classified into five types based on sequence and structural homology: type I IRES of the enterovirus group with poliovirus as prototype, type II IRES of the cardiovirus/aphthovirus group with encephalomyocarditis virus (EMCV) and FMDV as prototypes type III IRES of hepatitis A virus (HAV), and type IV IRES of porcine teschovirus (PTV) (Borman et al, 1997;Brown et al, 1991;Jackson et al, 1994;Pisarev et al, 2004). Sweeney et al (2012) and colleagues recently identified a fifth IRES class among members of the Kobuvirus, Salivirus and Oscivirus genera. The nucleotide sequence identity among IRES elements of the same type is only moderate, but their predicted secondary structure is highly conserved.…”
Section: Introductionmentioning
confidence: 99%
“…These elements are cis-acting RNA regulatory sequences endowed with the capacity to govern cap-independent translation initiation in mRNAs that are translated when cap-dependent translation is compromised. Subsequent studies demonstrated that IRES elements drive internal initiation of translation in the RNA of all members of the Picornaviridae family (Bakhshesh et al, 2008;Borman and Jackson, 1992;Brown et al, 1991;Hinton and Crabb, 2001;Hinton et al, 2000;Kaku et al, 2002;Kuhn et al, 1990;Nateri et al, 2000;Sweeney et al, 2012;Willcocks et al, 2011;Yu et al, 2011b). The genome of other RNA viruses also contains IRES elements, as illustrated by hepacivirus, pestivirus, dicistrovirus, retrovirus Tsukiyama-Kohara et al, 1992;Vallejos et al, 2010;Wilson et al, 2000), as well as some RNA viruses infecting plants and protozoa (reviewed in Martinez-Salas et al, 2012).…”
Section: Features Of the Picornavirus Untranslated Regionmentioning
confidence: 99%
“…These elements are diverse in primary sequence and secondary RNA structure, being classified into five different types [16]. Functionally related picornavirus IRESs harbor a common RNA structure core and sequence motifs maintained by evolutionary conserved covariant substitutions [17].…”
Section: Introductionmentioning
confidence: 99%